Serum CD73 is a prognostic factor in patients with metastatic melanoma and is associated with response to anti-PD-1 therapy - Dirk Schadendorf; Celeste Lebbe; Teresa Amaral; Benjamin Weide; Mariaelena Capone; Gabriele Madonna; Lucia Festino; Reinhard Dummer; Domenico Mallardo; Paolo A Ascierto; Piotr Rutkowski; Jason John Luke; et al. (Journal for ImmunoTherapy of Cancer)
Background Inhibitors of immune checkpoint programmed cell death protein 1 (PD-1) receptor on T cells have shown remarkable clinical outcomes in metastatic melanoma. However, most patients are resistant to therapy. Production of extracellular adenosine, via CD73-mediated catabolism of AMP, contributes to suppress T-cell-mediated responses against cancer. In this study, we analyzed the expression and activity of soluble CD73 in sera of patients with melanoma undergoing anti-PD-1± cytotoxic T-lymphocyte-associated antigen 4 therapy.Methods Soluble CD73 expression and activity were retrospectively analyzed in serum of a total of 546 patients with melanoma from different centers before starting treatment (baseline) with anti-PD-1 agents, nivolumab or pembrolizumab, and compared with those of 96 healthy subjects. The CD73 activity was correlated with therapy response and survival of patients.Results Patients with melanoma show significantly higher CD73 activity and expression than those observed in healthy donors (p<0.0001). Elevated pretreatment levels of CD73 activity were associated with non-response to therapy with nivolumab or pembrolizumab. During treatment, levels of soluble CD73 activity remain unchanged from baseline and still stratify clinical responders from non-responders. High levels of serum CD73 enzymatic activity associate with reduced overall survival (OS; HR=1.36, 95% CI 1.03 to 1.78; p=0.03) as well as progression-free survival (PFS; HR=1.42, 95% CI 1.13 to 1.79, p=0.003). Further, the multivariate Cox regression analysis indicates that serum CD73 activity is an independent prognostic factor besides serum lactate dehydrogenase levels and the presence of brain metastases for both OS (p=0.009) and PFS (p=0.001).Conclusion Our data indicate the relevance of serum CD73 in patients with advanced melanoma receiving anti-PD-1 therapy and support further investigation on targeting CD73 in combination with anti-PD-1 antibodies.